AEROACOUSTICS INVESTIGATIONS OF A WIND TURBINE FOR DIFFERENT VELOCITIES USING COMPUTATIONAL FLUID DYNAMICS SOFTWARE - KEPEKCI, Haydar; ZAFER, Baha; GUVEN, Hasan Rıza (MATTER: International Journal of Science and Technology, 2019)
The main reason why wind farms cannot be installed close to people’s habitats is the noise pollution they generate while working. This paper studies a flow area, which is analyzed on the 3D S809 blade profile using the SST k-ω turbulence model to calculate the near-field flow of wind turbines. The attached a time-dependent flow field factors in Ffowcs-Williams and Hawkings (FW-H) equating Sound Pressure Level (SPL) was calculated for different velocities as 5.4 m/s and 7 m/s from the microphone placed in the computational domain to be analyzed. In this study, the NREL phase VI small scale (12%) baseline airfoil type was used. The acoustic results and torque values obtained from the analyzes were compared both with the data in the literature and among themselves. As a result; one of the calculated torque values was under the literature amount. This differentiation maybe since the analysis given in the literature contains a higher number of mesh cells. SolidWorks software was used for airfoil drawing, and Ansys Fluent software was preferred for analysis in research. This article involves a subject that is on the near-field flow of wind turbines. This sample of 3D S809 has nearly 2.2 million elements and solves compressible fluid flow with the SST model. The same mesh geometry was used in both analyses.